COMPARISON OF SECONDARY AC-IOL IMPLANTATION ON APHAKIA PATIENTS WITHOUT CAPSULAR SUPPORT AFTER PARS PLANA VITRECTOMY VERSUS COMPLICATED CATARACT SURGERY - Widya Ardhana Reswari; Prili Olda; Erin Arsianti; Elisa Manueke; Supanji Supanji (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and objectiv: Capsular support is often absent in cases of aphakia secondary to ocular trauma or previous complicated intraocular surgery. This study aims to compare the short-term efficacy and safety of secondary AC IOL implantation for aphakia patients who underwent pars plana vitrectomy and complicated cataract surgery Method: Retrospective, comparative, case series of 72 aphakic eyes without capsular support after pars plana vitrectomy (Group 1 =37 eyes) and complicated cataract surgery (Group 2=35 eyes) who underwent secondary AC-IOL implantation (Iris Claw and Anterior Chamber) in Yap Eye Hospital and Air Force Central Hospital Hardjolukito. Basic characteristics such as age, sex, laterality, visual acuity, intraocular pressure (IOP), central corneal thickness, endothelial count, axial length, anterior chamber depth and keratometry were recorded Results: There were no statistically differences at baseline characteristics between the two groups. Despite the proportion difference of lens type used in both group (p=0.04), the mean visual acuity outcome at day 1 and month 3 were found similar. However, on day 7 and month 1 the difference of postoperative visual acuity showed a trend. The difference of postoperative mean IOP was also not significant at day 1, month 1 and month 3, but showed a trend in day 7 (p=0.06). The proportion of complication cases were found different in both group (p=0.01), with secondary glaucoma was found highest (18%). Conclusion: The outcomes of secondary anterior chamber IOL implantation after pars plana vitrectomy and complicated cataract surgery were found similar, although there was a significant difference in the proportion of complication in both groups